Drought from the 1970s to the 1990s and its Influence in the Tropical City of Beni, Eastern DR Congo - Moïse Musubao Kapiri; Jonathan Ahadi Mahamba; Rodriguez Kakule Amani; Gloire Kayitoghera Mulondi; Walere Muhindo Sahani (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Regional and local climate variability has serious consequences on water resources, ecosystems, and socio-economic activities. With the inexistence of rainfall stations, it is important to reconstruct the past climate with existing data and explore new possibilities for monitoring future climate evolution in the tropical city of Beni. The objective of this paper is to date the 1970-1990 drought and determine the rainfall trend in the tropical city of Beni. To this purpose, a 45-year rainfall time series (period 1974-2019) was analyzed using the Standardized Precipitation Index (SPI). The results of the paper indicate that the average annual rainfall ranges from 693 to 3080 mm with an average of 1827 ± 480.65 mm. The Hubert segmentation procedure applied to the rainfall series reveals three breaks (sub-periods): 1974-1979 (mean 1205.7 mm), 1980-2007 (mean 1736.68 mm), and 2008-2019 (mean 2348.01 mm). After the 2000s, the analysis shows an increasing trend in rainfall. A rainfall deficit of 35.20% is recorded during the period 1974-1979 compared to the period 1980-2007 and 22.61% for the period 1980-2007 compared to the period 2008-2019. The results of this study demonstrate that the city of Beni would have suffered from the drought of the years 1970-1990. Future research should focus on the future evolution of rainfall. However, understanding this future evolution requires long-term data, which is not the case for the tropical city of Beni. Therefore, there is a need for policymakers in collaboration with scientific actors to install meteorological stations to collect climate data.